A novel in vivo assessment of fluid dynamics on aortic valve leaflet using epi‐aortic echocardiogram. Issue 2 (31st January 2020) - Hayashi, Hideyuki; Akiyama, Koichi; Itatani, Keiichi; DeRoo, Scott; Sanchez, Joseph; Ferrari, Giovanni; Colombo, Paolo C.; Takeda, Koji; Wu, Isaac Y.; Kainuma, Atsushi; Takayama, Hiroo
Abstract: Background: Mechanical stress caused by blood flow, such as wall shear stress (WSS) and its related parameters, is key moderator of endothelial degeneration. However, an in vivo method to measure WSS on heart valves has not been developed. Methods: We developed a novel approach, based on vector flow mapping using intraoperative epi‐aortic echocardiogram, to measure WSS and oscillatory shear index (OSI) on the aortic valve. We prospectively enrolled 15 patients with normal valves, who underwent coronary artery bypass graft. Results: Systolic WSS on the ventricularis (2.40 ± 0.44 Pa [1.45‐3.00 Pa]) was higher than systolic WSS on the fibrosa (0.33 ± 0.08 Pa [0.14‐0.47 Pa], P < .001) and diastolic WSS on the ventricularis (0.18 ± 0.07 Pa [0.04‐0.28 Pa], P < .001). Oscillatory shear index on the fibrosa was higher than on the ventricularis (0.29 ± 0.04 [0.24‐0.36] vs 0.05 ± 0.03 [0.01‐0.12], P < .001). A pilot study involving two patients with severe aortic regurgitation showed significantly different values in fluid dynamics. Conclusion: Vector flow mapping method using intraoperative epi‐aortic echocardiogram is an effective way of measuring WSS and OSI on normal aortic leaflet in vivo, allowing for better understanding of the pathophysiology of aortic valve diseases.